Evaluation of the relationship between infiltrating lymphocytes and inflammatory response in breast cancer: A systematic review (Research, Society and Development, 2023)
Breast cancer is the most incident type of cancer in women worldwide and delays in its diagnosis and treatment potentially reduce survival rates. It is a heterogeneous disease and rich in stromal and inflammatory immune cells and soluble factors in its tumor microenvironment. Tumor infiltrating lymphocytes (TILs) are components of this inflammatory microenvironment and the density of TILs has proved to be an important tool in mediating the effectiveness of immunomodulatory therapies and in the prognosis of residual disease after neoadjuvant chemotherapy treatment. The aim of this study was to evaluate the relation between infiltrating lymphocytes and the inflammatory response in women with breast cancer. This is a descriptive, qualitative, systematic literature review study. The databases used to search for articles were Pubmed, Scielo and Cochrane, using the keywords “infiltrating lymphocytes, inflammatory response and breast cancer”, and the Boolean operator “And”. Complete articles published between 2012 and 2022 in English, Portuguese and Spanish, were included. The review was performed according to the PRISMA recommendation (Key Items for Reporting Systematic Reviews and Meta-analysis) and the Joana Briggs Institute (JBI) Appraisal Tools to assess the risk of selected studies. 91 articles were found, of which 17 were selected to be part of this review. The reviewed studies reveal a strong correlation between tumor stromal infiltrating lymphocytes (TILs) and tumor immune response, which may become an important measure for detecting the prognosis and survival of the disease.